Tendencias Recientes en la Producción, Comercio y Consumo de Mango en el Mundo y en los Estados Unidos - Edward A. Evans (EDIS, 2009)
FE790 is the Spanish language version of FE718, “Recent Trends in World and U.S. Mango Production, Trade, and Consumption,” a 7-page article by Edward A. Evans. It summarizes some of the recent trends in world and U.S. mango production, trade, and consumption. Includes references. Published by the UF Department of Food and Resource Economics, November 2008.